Effects of fat crystal networks on the stability and whipping properties of non-dairy oil-in-water emulsions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Manawatū, New Zealand. EMBARGOED until 21st February 2027. - Zhang, Sheng (Massey University, 2024)
Non-dairy whippable oil-in-water (O/W) emulsions have gained increasing attention from food companies and consumers in recent years due to their greater sustainability and lower energy density. This study investigated functional aspects of whippable non-dairy emulsions, focusing on the unique properties of coconut oil as the lipid component and monoglyceride emulsifiers. The study attempted to address longing-standing challenges relating to the stability and performance of these emulsions and emphasised the vital role of the fat crystal network (FCN), with a particular focus on achieving whippable formulations and low-fat contents. The study explored several compositional and processing variables, including fat content, homogenisation pressure, rate of cooling, Unsaturated monoglycerides UM concentrations, and sugar addition.--Shortened abstract
Embargoed until 21st February 2027
Keywords: 300607 Food technology